Suitability of Hydraulic Disk Brakes for Passive Actuation of Upper-Extremity Rehabilitation Exoskeleton - Arno H. A. Stienen; Edsko E. G. Hekman; Alfred C. Schouten; Frans C. T. van der Helm; Herman van der Kooij (Applied Bionics and Biomechanics)
Passive, energy-dissipating actuators are promising for force-coordination training in stroke rehabilitation, as they are inherently safe and have a high torque-to-weight ratio. The goal of this study is to determine if hydraulic disk brakes are suitable to actuate an upper-extremity exoskeleton, for application in rehabilitation settings. Passive actuation with friction brakes has direct implications for joint control. Braking is always opposite to the movement direction. During standstill, the measured torque is equal to the torque applied by the human. During rotations, it is equal to the brake torque. Actively assisting movement is not possible, nor are energy-requiring virtual environments. The evaluated disk brake has a 20 Nm bandwidth (flat-spectrum, multi-sine) of 10 Hz; sufficient for torques required for conventional therapy and simple, passive virtual environments. The maximum static output torque is 120 Nm, sufficient for isometric training of the upper extremity. The minimal impedance is close zero, with only the inertia of the device felt. In conclusion, hydraulic disk brakes are suitable for rehabilitation devices.